Studies on Spanish Poetry in Honour of Trevor J. Dadson : Entre Los Siglos de Oro y el Siglo XXI. - Torres, Isabel (Monografías A Ser., 2019)
A collection of essays on Spanish poetry honouring a distinguished British Hispanist.